2015
DOI: 10.1155/2015/730606
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Acute Anterior Ischemic Optic Neuropathy in a Patient with an Already Established Diagnosis of Bilateral Optic Disc Drusen

Abstract: Optic disc drusen (ODD) are calcific deposits that form in the optic nerve head secondary to abnormalities in axonal metabolism and degeneration. Anterior ischemic optic neuropathy, central retinal artery, and vein occlusion are among the rare vascular complications of disc drusen. We reported the clinical course of a 51-year-old patient with a unilateral acute nonarteritic anterior ischemic optic neuropathy (NAION) who received the diagnosis of bilateral optic disc drusen five years earlier and thereby reiter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Regarding ODD and prelaminar hyperreflective lines, this is unlikely for several reasons: (1) Previous case reports and one larger follow-up study have described cases of presence of ODD before onset of NA-AION years later. 28,29 (2) ODD is believed to be inherited in an irregular autosomal dominant manner. 30 (3) Studies have found patients with ODDassociated NA-AION (ODD-AION) to be younger than NA-AION patients, indicating ODD being an independent risk factor to NA-AION.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ODD and prelaminar hyperreflective lines, this is unlikely for several reasons: (1) Previous case reports and one larger follow-up study have described cases of presence of ODD before onset of NA-AION years later. 28,29 (2) ODD is believed to be inherited in an irregular autosomal dominant manner. 30 (3) Studies have found patients with ODDassociated NA-AION (ODD-AION) to be younger than NA-AION patients, indicating ODD being an independent risk factor to NA-AION.…”
Section: Discussionmentioning
confidence: 99%
“…Though quite rare, NAION, central retinal artery and vein occlusion have been reported to occur in cases with ONHD. [13][14][15][16][17][18][19][20][21] The exact mechanism by which ONHD causes NAION is uncertain. By tightening the disc space drusen can increase the susceptibility to optic nerve head ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] The recent published cases have additional risk factors such as diabetes mellitus that could cause NAION apart from ONHD. 21 It is therefore very difficult to directly associate ONHD with NAION. Our report has two contributions to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ONHD appear to be at increased risk of non-arteritic anterior ischaemic optic neuropathy (NAION), although the risk is hard to quantify in this small and varied population. 24,123,124 Patients are typically younger and have more favourable outcomes than NAION patients without ONHD. Other risk factors for NAION and clinical features such as the risk of bilateral disease, and visual field defects are similar in those with or without ONHD.…”
Section: Anterior Ischaemic Optic Neuropathymentioning
confidence: 99%